2015
DOI: 10.4049/jimmunol.1401515
|View full text |Cite
|
Sign up to set email alerts
|

Profiling T Cell Activation Using Single-Molecule Fluorescence In Situ Hybridization and Flow Cytometry

Abstract: Flow cytometric characterization of antigen-specific T cells typically relies on detection of protein analytes. Shifting the analysis to detection of RNA would provide several significant advantages, which we illustrate by developing a new host immunity-based platform for detection of infections. Cytokine mRNAs synthesized in response to ex vivo stimulation with pathogen-specific antigens are detected in T cells with single molecule-fluorescence in situ hybridization followed by flow cytometry. Background from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 12 publications
2
36
0
Order By: Relevance
“…To reduce the magnification and increase the visible area while still viewing individual RNAs, we applied 4-rounds of clampFISH to mouse kidney samples and probed for PODXL mRNA, an gene that is highly expressed in podocytes 18 , and observed specific expression of clampFISH signal in the appropriate regions (Figure 2b, Supplementary Figure 4). Interestingly, clampFISH further revealed that PODXL also expressed in the kidney endothelium, a signal that was only faintly visible by single molecule RNA FISH, but was clearly detected by clampFISH at low magnification (Figure 2b) consistent with previous findings that PODXL is expressed at low levels in the kidney endothelium 19 .Another important application that clampFISH enables is flow cytometry based measurement of RNA expression, an application for which single molecule RNA FISH typically does not produce enough signal 20,21 . We applied clampFISH to a mixed population of MDA-MB Figure 6).…”
supporting
confidence: 72%
“…To reduce the magnification and increase the visible area while still viewing individual RNAs, we applied 4-rounds of clampFISH to mouse kidney samples and probed for PODXL mRNA, an gene that is highly expressed in podocytes 18 , and observed specific expression of clampFISH signal in the appropriate regions (Figure 2b, Supplementary Figure 4). Interestingly, clampFISH further revealed that PODXL also expressed in the kidney endothelium, a signal that was only faintly visible by single molecule RNA FISH, but was clearly detected by clampFISH at low magnification (Figure 2b) consistent with previous findings that PODXL is expressed at low levels in the kidney endothelium 19 .Another important application that clampFISH enables is flow cytometry based measurement of RNA expression, an application for which single molecule RNA FISH typically does not produce enough signal 20,21 . We applied clampFISH to a mixed population of MDA-MB Figure 6).…”
supporting
confidence: 72%
“…Our inexpensive smFISH technique for quantitating vRNA functions at an efficiency that is on par with a proprietary branched DNA amplification method recently used to detect single HCV vRNAs (35), and can be integrated with rapid-staining techniques for increased throughput (94). This toolbox can be extended by offering simultaneous single-cell protein and RNA-level imaging when combined with fluorescent reporter viruses and integration with flow-based quantification (95, 96), or by simultaneous monitoring of two viral mutants with appropriate reporter sequences to study questions of drug resistance and superinfection (97). …”
Section: Discussionmentioning
confidence: 99%
“…The small sample size limits the ability to assess cell population behaviors and precludes identification of rare cell subsets displaying particular expression patterns. To overcome the limitations of the microscopy-based platform, we adapted sm-FISH to flow cytometry 7–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unique properties of flow cytometry, our flow-cytometry-based embodiment of sm-FISH, which we call FISH-Flow 7–8 , constitutes an important advancement over microscopy-based sm-FISH for the study of single-cell gene expression. With its ability to analyze thousands of cells simultaneously, FISH-Flow can be used to distinguish cells producing particular mRNAs (as few as ten molecules of mRNA per cell 7 ) from cells that do not. An example of parallel microscopy-based sm-FISH and FISH-Flow analysis is shown in Figure 1b,c.…”
Section: Introductionmentioning
confidence: 99%